Virtue ethics and the unsettled ethical questions in controlled human infection studies - Poomkudy, Jeffrey T. (Bioethics, 2024)
Controlled human infection studies (CHIs) involve the intentional infection of human subjects for a scientific aim. Though some past challenge trials have involved serious ethical abuses, in the last few decades, CHIs have had a strong track record of safety. Despite increased attention to the ethics of CHIs during the COVID-19 pandemic, CHIs remain controversial, and there has been no in-depth treatment of CHIs through the lens of virtue ethics. In this article, we argue that virtue theory can be helpful for addressing CHIs that present a constellation of controversial, unresolved, and/or under-regulated ethical issues. We begin with some brief background on virtue ethics. We then substantiate our claim that some CHIs raise a constellation of ethical issues that are unresolved in the ethics literature and/or lack adequate regulatory guidance by demonstrating that CHIs can present indeterminate social value, risks to third parties, limitations on the right to withdraw from research, and questions about the upper limit of allowable risk. We argue that the presence of a virtuous investigator, with virtues such as prudence, compassion, and integrity, is especially important when these unresolved research ethics issues arise, which is the case for certain types of controlled human infection studies. We use the historical example of Walter Reed and the Yellow Fever Commission to illustrate this claim, and we also highlight some contemporary examples. We end by sketching some practical implications of our view, such as ensuring that investigators with experience running CHIs are involved in novel CHI models.